2016
DOI: 10.1037/dev0000216
|View full text |Cite
|
Sign up to set email alerts
|

The developmental course of supportive dyadic coping in couples.

Abstract: Drawing from a relational developmental systems (RDS) perspective (Lerner, Agans, DeSouza, & Gasca, 2013) and data from 1,427 continuously partnered young adult and midlife mixed-sex couples over the first 5 years of the German Panel Analysis of Intimate Relationships and Family Dynamics (pairfam), this study examined the developmental course of supportive dyadic coping, or the frequency with which one provides practical and emotional support when his or her partner encounters stress. Latent change score (LCS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 63 publications
5
41
0
Order By: Relevance
“…In sum, men's CoF seems to be one factor that affects the long‐term development of a couple's supportive dyadic coping in a positive way. Given that supportive dyadic coping, on average, erodes across time (Johnson et al, ) men's CoF might be one factor that helps couples to maintain high relationship functioning in the long run. The current results therefore expand on previous results and suggest that interpersonal differences in men's CoF are not only associated with concurrent supportive dyadic coping but seem to be also a crucial resource for maintaining adequate supportive dyadic coping across a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In sum, men's CoF seems to be one factor that affects the long‐term development of a couple's supportive dyadic coping in a positive way. Given that supportive dyadic coping, on average, erodes across time (Johnson et al, ) men's CoF might be one factor that helps couples to maintain high relationship functioning in the long run. The current results therefore expand on previous results and suggest that interpersonal differences in men's CoF are not only associated with concurrent supportive dyadic coping but seem to be also a crucial resource for maintaining adequate supportive dyadic coping across a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that dyadic coping is a characteristic of well‐functioning intimate relationships (Bodenmann & Cina, ). Given that relationship functioning tends to erode over time (Johnson, Horne, & Galovan, ; Kamp Dush, Taylor, & Kroeger, ) it is crucial to understand how couples can sustain good relationship functioning in the long run (e.g., maintaining high levels of dyadic coping). This study targets this question by investigating clarity of other's feelings (hereafter referred as “CoF”) as one potential key predictor for long‐term support provision in intimate relationships.…”
Section: Clarity Of Other's Feelingsmentioning
confidence: 99%
See 2 more Smart Citations
“…We do this for several reasons. As Revenson and DeLongis () suggested, dyadic coping occurs in response to “a specific stressor.” Particularly since the development of measures such as the Dyadic Coping Inventory (Bodenmann, ), many studies have explored dyadic coping in what we might call a “generic” way, that is, outside of the context of a specific stressor (e.g., Johnson, Horne, & Galovan, ). When a specific stressor or stress appraisal is not part of the conceptualization, assessment of dyadic coping runs the risk of becoming a stand‐in for other well‐researched constructs, such as conflict management and couple intimacy.…”
Section: Review Of Recent Research and Theoretical Perspectives On Dymentioning
confidence: 99%